2003
DOI: 10.1289/ehp.5704
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the allergic potential of food protein extracts and proteins on oral application using the brown Norway rat model.

Abstract: The need for widely accepted and validated animal models to test the potential allergenicity and potency of novel (biotechnology-derived) proteins has become an important issue for their safety evaluation. In this article, we summarize the results of the development of an oral sensitization protocol for food proteins in the rat. Young Brown Norway rats were exposed to either various purified allergenic proteins (e.g., ovalbumin, partly purified), a whole food (cow's milk), or total protein extracts (hen's egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 29 publications
(20 reference statements)
1
26
0
Order By: Relevance
“…The Brown Norway rat has a genetic predisposition to allergy development and has been successfully used as a model to induce allergic IgG and IgE responses to oral antigens (21)(22)(23)(24). Given the contradictory evidence of the role of breast-feeding in allergy development, we assessed at weaning (when TGF-␤ is still present in the diet) and postweaning (when TGF-␤ was no longer present in the diet), the immune response profile of allergy-prone Brown Norway rat pups either suckled naturally or fed formula with and without supplementation with the maternal milk cytokine TGF-␤.…”
mentioning
confidence: 99%
“…The Brown Norway rat has a genetic predisposition to allergy development and has been successfully used as a model to induce allergic IgG and IgE responses to oral antigens (21)(22)(23)(24). Given the contradictory evidence of the role of breast-feeding in allergy development, we assessed at weaning (when TGF-␤ is still present in the diet) and postweaning (when TGF-␤ was no longer present in the diet), the immune response profile of allergy-prone Brown Norway rat pups either suckled naturally or fed formula with and without supplementation with the maternal milk cytokine TGF-␤.…”
mentioning
confidence: 99%
“…In conclusion the results obtained to date indicate that the BN rat might be a useful animal model in which to study the potential oral allergenicity of novel food proteins (Knippels and Penninks 2003). However, further testing with either whole food or with additional purified non-, weak-, and strongallergenic proteins is needed for a more indepth evaluation of this BN rat model.…”
Section: Oral and Intraperitoneal Exposure Of Brown Norway Ratsmentioning
confidence: 88%
“…It is conceivable that the spontaneous granulomatous inflammation was caused as a kind of allergic response. It was found that BN rats continuously administered OVA, whole protein extracts of hen's egg white or cow's milk are sensitized to those proteins [13]. In addition, BN rats were also susceptible to sensitization following topical exposure to the low molecular weight chemical, trimellitic anhydride [4].…”
Section: Discussionmentioning
confidence: 99%